Evaluation of Staff Nurses’ performance at Primary Health Care Centers in Baghdad City - Hadi, Ali; Fadhil, Mohammed (Iraqi National Journal of Nursing Specialties, 2020)
Objectives: This study aimed to evaluate the performance of staff nurses at primary health care centers in Baghdad city and to compare them with their demographic characteristics of age, gender and education.Methodology: A descriptive design was carried out at Baghdad City’s primary health care centers from January 2nd 2019 to May 1st 2020. An instrument was developed for the purpose of the study. A non-probability, multi-stage purposive sample of (52) staff nurses was recruited from nurses working at primary health care centers in Baghdad City. The instrument is used to evaluate staff nurses’ performance which includes (62) items. These items are divided to (13) main domains related to evaluation of work quantity, work quality, punctuality of work, initiative, creativity and judgment, commitment to program goals, work with others ability, express self verbally and in writing ability, planning and organization, crisis response, solve problems ability, professional Skills in present activity, supervisory skills and response to supervision as dimensions of staff nurses’ performance. Questionnaire content validity is determined by a panel of (10) experts. Reliability was determined through Inter-observer technique. Data are collected by using the study instrument and the observation technique as data collection method. Data are analyzed using a systematic approach to statistical analysis of frequencies, percentages, total scores and ranges and inferential statistical data analysis of t- test and analysis of variance.Results: The majority of the staff nurses have poor level of overall evaluation of the dimensions of staff nurses’ performance.Recommendations: Periodic and regular evaluation and follow-up to staff nurses’ performance of the evidence-based practices have to be maintained at the primary health care centers.